Kinetic modelling of combined ultrasonication and Soxhlet based extraction of lipids from passion fruit seed using ethanol as solvent - H. Chutia; C.L. Mahanta (Grasas y Aceites)
The aim of this study was to understand the extraction phenomena of oil from passion fruit seeds (PFS) using Soxhlet, ultrasonic-assisted extraction (UAE), and combined UAE-Soxhlet (UAES) methods and to investigate the physicochemical properties of the oil. The effect of solid-liquid ratio, temperature, and time of the UAE treatment on PFS oil (PFSO) yield was investigated and optimized. Phenomenological model parameters, viz. washing constant (0,807–1,139×10–1min–1) was faster than the diffusion constant parameter (5.0–5.4×10–3min–1) throughout the extraction process, and the washing constant was the highest for UAES. The composition of phenolics and fatty acids in the optimized oil extract was investigated by HPLC and GC, respectively. The comparison of the quality parameters of the extracted oils revealed that the combination of ultrasound and Soxhlet extraction is a viable alternative extraction procedure for obtaining better quality. The phenomenological model with combined extraction could be recommended for modelling extraction kinetics for better quality products and could be used for industrial purposes.